A Method of Manufacturing a Long-Acting Medicinal Film Containing VEGF - I. S. Kurganskiy (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. The development of new methods for delivering biologically active substances to the surgical site is a promising area of modern surgery. One of the biologically active substances used to stimulate regeneration is the vascular endothelial growth factor (VEGF). The search for ways to gradually and over a long period of time deliver VEGF to the surgical site is a promising area of research.Aim. To develop a method for delivering VEGF to the surgical site and to assess its elimination in the early postoperative period.Materials and methods. The study included 78 male Wistar rats at the age of 10 months. All animals underwent reconstructive surgery on the trachea, the animals were divided into 3 groups: group 1 – without a medicinal film, group 2 – with a medicinal film of prolonged action, group 3 – with a medicinal film of prolonged action containing VEGF. Blood sampling was carried out on days 1, 3, and 21 of the study, using the method of enzyme-linked immunosorbent assay to determine the level of VEGF in blood plasma, the unit of measurement was pg/ml.Results. A long-acting medicinal film containing VEGF has been developed. It was revealed that the use of a medicinal film containing VEGF significantly increases the VEGF index in blood plasma by 26 times starting from the first day of the study and remained high throughout the study.Conclusion. The results obtained indicate the effectiveness of the developed medicinal film of prolonged  action. Elimination of VEGF starts from the first day of the study and lasts up to 21 days. High VEGF indices,  according to the authors, are associated with the exogenous introduction of VEGF into the animal organism in the form of a prolonged-action film and the induction of endogenous VEGF in rats.